Towards an Abundance Estimate for New Zealand Fur Seal in New Zealand - Hall A; Chilvers BL; Weir JS (John Wiley and Sons Ltd, Hoboken, USA, 2025)
A lack of population abundance and trajectory data is a conservation and management issue relevant to numerous pinniped species, many of which are exposed to a variety of threats. New Zealand fur seal (Arctocephalus forsteri; ‘NZFS’) populations in different parts of New Zealand have experienced both substantial increases and decreases to their abundance over the last 50 years, since the last nationwide census. Here, existing data and stage-structured matrix modelling were used to provide a contemporary nationwide estimate of NZFS abundance. Graphical depictions demonstrate the spatial inconsistencies in NZFS monitoring in New Zealand through time. A minimum population estimate of 131,338–168,269 NZFS was calculated by combining the most recently available pup production data from around New Zealand and using established multipliers. A second estimate of 181,646–239,473 NZFS was calculated using stage-structured matrix models to project contemporary abundance. Inconsistent NZFS population monitoring and sparse vital rate data for New Zealand's NZFS limited this study, and both population ranges are likely underestimates. However, they still represent substantial increases on the most cited nationwide abundance figure (100,000 NZFS). From these findings, we suggest that a regularised program of monitoring is adopted for New Zealand's NZFS, as has been achieved for similar species in other countries. This would both aid in the management of NZFS in the face of emerging risks, such as H5N1 avian influenza, and enable their use as a sentinel for the health of New Zealand's marine ecosystems.
Keywords: Arctocephalus forsteri; matrix modelling; New Zealand fur seal; population modelling; range wide abundance; sentinel species; stage structured modelling